2011
DOI: 10.1590/s1984-46702011000100014
|View full text |Cite
|
Sign up to set email alerts
|

Morphological description of Dipturus mennii (Chondrichthyes: Elasmobranchii: Rajidae) and its differentiation from Dipturus trachyderma

Abstract: Squamation patterns and skeletal anatomy (neurocranium, visceral arches, synarcual cartilage, scapulocoracoid, puboischiadic bar, and mixopterigium) of Dipturus mennii Gomes & Paragó, 2001 are described as a contribution to our limited knowledge of the anatomy of species of Dipturus Rafinesque, 1810. The hyoid and branchial arches, as well as the synarcual cartilage, are described for the first time in this species. We provide morphological comparisons of this species with Dipturus trachyderma (Krefft & Stehma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 14 publications
1
9
0
1
Order By: Relevance
“…The fleshy integument between the proximal and distal clefts found in A. cyclophora is not internally associated to a cartilaginous element, differing from the component terminal bridge described in most skates between the proximal and distal clefts (Hulley, ; Ishiyama, ; Moreira, Gomes, & Carvalho, ; Stehmann, ). Therefore, the clasper of A. platana and A. castelnaui are more similar to each other than to A. cyclophora by presenting a slender projection and a fleshy integument that conceals a thin spike (internally supported by the accessory terminal 2 cartilage).…”
Section: Discussionmentioning
confidence: 91%
“…The fleshy integument between the proximal and distal clefts found in A. cyclophora is not internally associated to a cartilaginous element, differing from the component terminal bridge described in most skates between the proximal and distal clefts (Hulley, ; Ishiyama, ; Moreira, Gomes, & Carvalho, ; Stehmann, ). Therefore, the clasper of A. platana and A. castelnaui are more similar to each other than to A. cyclophora by presenting a slender projection and a fleshy integument that conceals a thin spike (internally supported by the accessory terminal 2 cartilage).…”
Section: Discussionmentioning
confidence: 91%
“…Do ponto de vista morfológico é um grupo muito uniforme, a maioria das espécies é bentônica e de distribuição geográfica restrita, com alto grau de endemismo, fatores que geram grande riqueza de espécies em levantamentos regionais, bem como dificuldade de identificação dos táxons (Ebert & Compagno, 2007). O conhecimento deste grupo no Brasil aumentou consideravelmente nos últimos anos com o incremento do esforço amostral em ambiente da borda do talude em grandes profundidades (Gomes & Paragó, 2001;Gomes & Picado, 2001;Gomes & Costa, 2003;Carvalho et al, 2005;Moreira et al, 2011;U.L. Gomes, com.…”
Section: Ordem Rajiformes (Raias-emplastro Raias-santa)unclassified
“…However, the presence of the accessory terminal I cartilage (Atr1) was erroneously reported by Menni (1971) and Leible (1987), as there is no equivalent structure in Zearaja species (Last & Gledhill, 2007 (Krefft & Stehmann, 1975) and subsequent description (Leible & Stehmann, 1987) included details of external and internal structures, such as neurocranium, pelvic girdles, scapulocoracoid and clasper; and where the presence of Atr1 and the sentinel (both absent in Zearaja) were reported. Moreira et al, (2011) found differences in the neurocranium, scapulocoracoid and clasper between D. menni and D. trachyderma, which was consistent with there being two separate species, even though some specimens of D. menni…”
Section: Skeletal Componentssupporting
confidence: 67%